The Middle Grades Principal: A Research Agenda - Dana L. Bickmore (Middle Grades Review, 2016)
Advocates for middle grades education suggest that principals are critical to the implementation of curriculum, instruction, assessment, and organizational structures that meet young adolescent needs. Yet, there is little evidence associating principal practices outlined by middle grades proponents to outcomes or how principals learn the knowledge and practices middle grades advocates propose. This essay explores the limited research connecting middle grades principal leadership with school and student outcomes, how middle school principals learn the practices outlined by proponents of middle grades education, and proposes a research agenda and questions about middle grades principal learning.
Keywords: Middle school principal; middle grades principal; principal preparation; principal professional development; middle grades education